Plasmid DNA encoding neutralizing human monoclonal antibody without enhancing activity protects against dengue virus infection in mice - Surachet Benjathummarak; Atsushi Yamanaka; Thanyaluk Krasae; Chonlatip Pipattanaboon; Subenya Injampa; Pannamthip Pitaksajjakul; Pongrama Ramasoota (Asian Pacific Journal of Tropical Medicine, 2021)
Objective: To evaluate the expression of DNA plasmid-harboring modified antibody gene that produces neutralizing human monoclonal antibodies against four serotypes of dengue virus (DENV) without enhancing activity in BALB/c mice. Methods: We constructed pFUSE-based vectors (pFUSE_1G7C2_ hVH and pFUSE_1G7C2_hVL) containing genes encoding the variable domains of the heavy or light chain of the anti-dengue virus antibody 1G7C2, a human IgG1 that has been characterized for its neutralizing activity to DENV-1-4. Leucine (L) at positions 234 and 235 on the Fc CH2 domain in pFUSE_1G7C2_hVH was mutated to alanine (A) (LALA mutation) by site direct mutagenesis, and the new plasmid was termed pFUSE_1G7C2_hVH_LALA. An equal amount of pFUSE_1G7C2_hVL and 1G7C2_hG1-LALA plasmids were co-transfected into Chinese hamster ovary cells (CHO-K1) and a single dose of 100 μg 1G7C2_hG1-LALA plasmid was intramuscularly injected, followed by electroporation in BALB/c mice. The secreted 1G7C2_hG1-LALA antibodies in cell culture supernatant and mouse serum were examined for their biological functions, neutralization and enhancing activity. Results: The co-transfection of heavy- and light-chain 1G7C2_ hG1-LALA plasmids in CHO-K1 cells produced approximately 3 900 ng/mL human IgG and neutralized 90%-100% all four DENV, with no enhancing activity. Furthermore, the modified human IgG was produced more than 1 000 ng/mL in mouse serum on day 7 post plasmid injection and showed cross-neutralization to four DENV serotypes. Subsequently, antibody production and neutralization decreased rapidly. Nevertheless, the secreted neutralizing 1G7C2_ hG1-LALA in mouse serum demonstrated complete absence of enhancing activities to all DENV serotypes. Conclusions: These findings reveal that a new modified 1G7C2_ hG1-LALA expressing plasmid based on gene transfer is a possible therapeutic antibody candidate against DENV infection.